Sugary drink consumption and cancer risk: results from NutriNet-Santé prospective cohort. (13th November 2019) - Chazelas, E; Srour, B; Kesse-Guyot, E; Julia, C; Deschamps, V; Galan, P; Hercberg, S; Latino-Martel, P; Deschasaux, M; Touvier, M
Abstract: Background: The objective was to assess the associations between the consumption of sugary drinks (sugar sweetened beverages and 100% fruit juices), artificially sweetened beverages and cancer risk. Methods: Overall, 101, 257 participants aged ≥18y (mean age: 42.2) from the French NutriNet-Santé cohort (2009-2017) were included. Consumptions of sugary drinks and artificially sweetened beverages were assessed using repeated 24h-dietary records, designed to register participants' usual consumption for 3, 300 different food and beverage items. Associations between beverage consumption and the risk of overall, breast, prostate and colorectal cancer were assessed by multi-adjusted Fine&Gray Hazard models, accounting for competing risks. Results: The consumption of sugary drinks was significantly associated with overall cancer risk (n = 2, 193 cases, sHRfor a 100mL/d increase=1.18, 95% confidence interval 1.10 to 1.27, P<.0001) and breast cancer risk (n = 693 cases, sHRfor a 100mL/d increase=1.22, 95% confidence interval 1.07 to 1.39, P = 0.004). The consumption of artificially sweetened beverages was not associated with cancer risk. In specific sub-analyses, the consumption of 100% fruit juice was significantly associated with overall cancer risk (n = 2, 193 cases, sHRfor a 100mL/d increase =1.12, 95% confidence interval 1.03 to 1.23, P = 0.007). Conclusions: In this large prospective study, the consumption of sugary drinks was positively associated with overall and breast cancer risks. Of note, 100% fruit juices were also positively associated with overall cancer risk. These results need replication in other large-scale prospective studies. They suggest that sugary drinks, which are massively consumed in Western countries, may potentially represent a modifiable risk factor for cancer prevention. Key messages: In this large prospective study (n = 101, 257), the consumption of sugary drinks (including 100% fruit juice) was associated with an increase in overall and breast cancer risk. In specific sub-analyses, 100% fruit juices were also associated with an increased risk of overall cancers. The consumption of artificially sweetened beverages was not associated with cancer risk.